Principals Leadership Styles and Teachers Job Performances in Secondary Schools of Omdurman locality, Sudan - Saifaldin Idris Onia; Alshafea Bakheit Alshafea (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
Leadership style is a particular behavior applied by a leader to motivate subordinates to achieve the objectives of the organization. Therefore, a leader in an institution can take any type of leadership style via the circumstances on the ground to reach the effective and efficient work in an organization. Hence, the aim of this study was to investigate the relationship between principals leadership styles and teachers job performances in secondary school of Omdurman locality, Sudan. In doing so, a descriptive research was employed. A sample size of 160, (85) male, and (75) female was responded. The data were collected through questionnaires and analyzed quantitatively using SPSS. The study showed that secondary schools principals frequently practice the democratic leadership style. There is strong significant relationship between leadership styles and teachers job performance. The researchers recommended that, principals should adopt democratic leadership style in their schools so that can lead to better performance.